Entrepreneurial News Sites as Worthy Causes? Exploring Readers' Motivations Behind Donating to Latin American Journalism. Issue 3 (16th March 2021) - Harlow, Summer
Abstract: This study uses surveys with readers of entrepreneurial news startups in seven Latin American countries to examine their motivations for donating to journalism. Using the donor–organization relationship from public relations scholarship as a framework, this study showed content, independent/objective journalism, and community were main motivating factors for donating. A lack of priority, and techno- and commercial-related concerns were reasons why readers did not donate. Professional and theoretical implications are discussed.